“One Long Frightening Climax”: Gillian Flynn’s Gone Girl and Lacan’s The Other Side of Psychoanalysis - Erica D. GALIOTO (E-REA)
“‘One Long Frightening Climax’: Gillian Flynn’s Gone Girl and Lacan’s The Other Side of Psychoanalysis argues that Lacan’s Seminar XVII: The Other Side of Psychoanalysis (1969-1970) may serve as an interpretive tool to analyze Gillian Flynn’s Gone Girl (2012) because the novel depicts subjectivity, discourse, and desire (and its absence) in ways that reflect Lacan’s projections for consumerist society, and it also provides an example of the psychoanalytic act as a necessary precursor to the exalted “other side of psychoanalysis.” As Lacan develops through the entirety of Seminar XVII and the character Amy Dunne portrays in Gone Girl, desire and access to jouissance emerge through the intervention of the signifier. Amy’s signifying act—her self-removal from a poorly-articulated field with no laws and no prohibition on enjoyment—hollows out a lack that provides access to a jouissance that is only made possible due to self-imposed boundaries, limits, and conditions.